Konstruksi Hukum Perlindungan Kurir Cash On Delivery (COD) Berbasis Asas Keadilan Dan Kepastian - Alifvio Bramandika Karindra; Rohaini, Rohaini; Kasmawati, Kasmawati; Sunaryo, Sunaryo; Adhan S, Sepriyadi (Lex Stricta : Jurnal Ilmu Hukum, 2025)
Digital transformation has given birth to new forms of work, one of which is couriers in the Cash on Delivery (COD) payment system which is a central actor in the Indonesian e-commerce ecosystem. The role of COD courier is not only as a delivery person, but also as a payment intermediary between business actors and consumers. However, this strategic position is not matched by adequate legal protection. COD couriers are often classified as “partners” by digital platforms, not formal workers, so they are in a legal vacuum that negates normative labor rights such as social security, work safety, and protection from consumer violence. This study aims to examine the legal position of COD couriers in the Indonesian labor law system and consumer protection, and analyze the application of the principles of justice and legal certainty to their existence. Using a normative juridical approach and theories of progressive law, responsiveness, and distributive justice, this research finds that the absence of explicit regulation of the legal status of couriers leads to unequal relations between couriers, platforms, and consumers. This research recommends a new hybrid regulation to ensure comprehensive protection for COD couriers, through normative recognition, fair employment contracts, violence reporting systems, and sectoral regulations that are responsive to the dynamics of digital work. The results of this research are expected to become a normative basis in the formation of regulations for the protection of informal workers in the digital economy era.